1985
DOI: 10.1186/1297-9686-17-2-225
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of French brown trout (Salmo trutta L): large geographical differentiation of wild populations and high similarity of domesticated stocks

Abstract: SummaryThe genetic variability of 7 fish-farm strains and 14 wild populations of brown trout was studied by electrophoretic analysis of 23 enzyme systems coded for by 52

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
2
10

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 13 publications
7
93
2
10
Order By: Relevance
“…Lack of gene flow concomitant with small effective population size resulted in a loss of genetic variation. Our GST value (GST= 0.198) proved lower than that found in brown trout from France (Krieg & Guyomard, 1985), Greece (Karakousis & Triantaphyllidis, 1990), Spain (Garcia-Mann et a!., 1991; Martinez et a!., 1993), Britain, Ireland, Norway, Sweden and Iceland (Ferguson, 1989), demonstrating that partitioning of gene diversity in southwest Germany differed from the situation observed in those quoted populations. Only Danish populations in tributaries of Lake Hald revealed still lower GST values (GST=O.O47) (Møller Hansen eta!., 1993), whereas GST= 0.11 was observed for Danish brown trout from the Limfjord catchment (Landbo & Persson, 1987cited in Møller Hansen et al, 1993.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Lack of gene flow concomitant with small effective population size resulted in a loss of genetic variation. Our GST value (GST= 0.198) proved lower than that found in brown trout from France (Krieg & Guyomard, 1985), Greece (Karakousis & Triantaphyllidis, 1990), Spain (Garcia-Mann et a!., 1991; Martinez et a!., 1993), Britain, Ireland, Norway, Sweden and Iceland (Ferguson, 1989), demonstrating that partitioning of gene diversity in southwest Germany differed from the situation observed in those quoted populations. Only Danish populations in tributaries of Lake Hald revealed still lower GST values (GST=O.O47) (Møller Hansen eta!., 1993), whereas GST= 0.11 was observed for Danish brown trout from the Limfjord catchment (Landbo & Persson, 1987cited in Møller Hansen et al, 1993.…”
Section: Discussioncontrasting
confidence: 61%
“…On a regional scale, there is only a weak correlation of genetic distances between local trout populations and geographical distances separating the respective stocks, suggesting a complex metapopulation structure for the species (Ryman, 1983;Ferguson, 1989). On a larger geographical scale, substantial differences have been reported between Mediterranean and Atlantic populations of France (Krieg & Guyomard, 1985) and between brown trout from the *Correspondence…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Osinov (1984) found (Ferguson & Fleming, 1983). This is more apparent if we consider the results of F-statistics (Table 4) French populations (Krieg & Guyomard, 1985).…”
Section: Locusmentioning
confidence: 96%
“…The first studies on the genetic structure of this species, using allozymic data, were performed on Population genetics studies on brown trout from Mediterranean drainages indicate that these populations are genetically distinct from Atlantic populations (Krieg & Guyomard, 1985;Guyomard, 1989; Garcia-Mann et a!., 1991). Another important feature of the Mediterranean populations, revealed by these studies, was their high degree of genetic diversity Karakousis & Triantaphyllidis, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, analyses of allozyme variation have revealed that genetically brown trout is one of the most highly structured fish species with more than 55 per cent of the total genetic diversity distributed among populations in some regions (Krieg & Guyomard, 1985;Apostolidis et al, 1996). Recent advances in *Correspondence tThis paper is dedicated to the memory of the late Dr Y. Karakousis by both his student (A.A.) and his professor (CT.).…”
Section: Introductionmentioning
confidence: 99%